Sistematización de la práctica pedagógica en la Fundación Artística y Cultural Chiminigagua. (2022)
This thesis is a systematization of the process of pedagogical practice by the master artist in training, at the Chiminigagua Artistic and Cultural Foundation of the municipality of Nemocón, Cundinamarca. The methodologies used in the teaching-learning process of the techniques for learning Colombian traditional dances are exposed. This document shows the logs, work plans, and audiovisual material compiled through the three periods of the pedagogical practice to reflect on the lived experience.